Intracellular serine protease of Bacillus subtilis: sequence homology with extracellular subtilisins. - Strongin, A Y (1978)
Intracellular serine protease was isolated from stationary-grown Bacillus subtilis A-50 cells and purified to homogeneity. The molecular weight of the enzyme is 31,000 +/- 1,000, with an isoelectric point of 4.3. Its amino acid composition is characteristically enriched in glutamic acid content, differing from that of extra-cellular subtilisins. The enzyme is completely inhibited with phenylmethylsulfonyl fluoride and ethylenediaminetetraacetic acid. Intracellular protease possesses negligible activity towards bovine serum albumin and hemoglobin, but has 5- to 20-fold higher specific activity against p-nitroanilides of benzyloxycarbonyl tripeptides than subtilisin BPN'. Esterolytic activity of the enzyme is also higher than that of subtilisin BPN'. The enzyme is sequence homologous with secretory subtilisins throughout 50 determined NH2-terminal residues, indicating the presence of duplicated structural genes for serine proteases in the B. subtilis genome. The occurrence of two homologous genes in the cell might accelerate the evolution of serine protease not only by the loosening of selective constrainst, but also by creation of sequence variants by means of intragenic recombination. Three molecular forms of intracellular protease were found, two of them with NH2-terminal glutamic acid and one minor form, three residues longer, with asparagine as NH2 terminus. These data indicate the possible presence of an enzyme precursor proteolytically modified during cell growth.